PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN PADA PT BCA Tbk (Fokus Ekonomi, 2011)
Company currently must begin to focus on delivering value (value) and increase customerloyalty. Loyalty means consumers returned again and again to conduct business transactions(purchases), although probably instead the company's product the best product on the market orhave the lowest prices. This "irrational" consumer behavior’s can be explained by a view that"good relations" (good relationships) which are established with the consumer, is the key to thesuccess of a company in retaining customers. The research goals are to test whether there isinfluence of Customer Relationship Management (CRM) to Customer Loyalty and to test howmuch influence Customer Relationship Management (CRM) to Customer Loyalty. This researchwas conducted by distributing questionnaires to the community in the city of Bandung, which hasever conduct banking transactions in PT BCA Tbk. Testing and processing of data using SPSS11.5 software with the help of regression and simple correlation method. The results showed thatcustomer relationship management affects customer loyalty.Key words: customer relationship management, customer loyalty.